1976
DOI: 10.1192/bjp.128.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Validation of a Predictive Scale for Subsequent Suicidal Behaviour in an Italian Sample

Abstract: A six-point prodictive scale for parasuicide repetition developed by Buglass and Horton (1974a) was tested on a group of patients admitted for parasuicide to a psychiatric ward of one of the city hospitals of Verona. The scale gave a range of probability of repetition within 12 months of 15 per cent at a score of o up to 45-5 per cent at the scores 3, 4, 5 and 6. Moreover the scale discriminated significantly between repeaters and non-repeaters. Items significantly associated with repetition in the Italian sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
3

Year Published

1979
1979
1993
1993

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 3 publications
1
11
0
3
Order By: Relevance
“…This unsatisfactory result suggests that the differential characteristics of our repeaters and non-repeaters have changed from the first 3 years to the next 3 years . This is confirmed by the results of the item analysis in the second sample as compared with those obtained in the first: only two items (diagnosis of sociopathy and less than 1 year at present address) were still significantly associated with repetition, while the three other items of the list (Garzotto et al (1976)) lost their discriminating power and four additional items (previous in-patient psychiatric treatment; previous parasuicide resulting in hospital admission, unemployment; criminal record) appeared as new discriminating factors.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…This unsatisfactory result suggests that the differential characteristics of our repeaters and non-repeaters have changed from the first 3 years to the next 3 years . This is confirmed by the results of the item analysis in the second sample as compared with those obtained in the first: only two items (diagnosis of sociopathy and less than 1 year at present address) were still significantly associated with repetition, while the three other items of the list (Garzotto et al (1976)) lost their discriminating power and four additional items (previous in-patient psychiatric treatment; previous parasuicide resulting in hospital admission, unemployment; criminal record) appeared as new discriminating factors.…”
Section: Discussionsupporting
confidence: 73%
“…The aim of the present study was to retest in a second sample of Italian parasuicide patients the validity of the six-item predictive scale for parasuicide repetition developed by Buglass & Horton (1974a) and to validate a new predictive scale consisting of the five items which had discriminated repeaters from non-repeaters in the first Italian sample (Garzotto et al (1976)). In this study, as well as in the previous one, 83 % of the repeaters were correctly identified (scoring 1 or more) by the six-item scale, while 17 % were missed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1975). Previous studies have attempted to identify stable characteristics which might distinguish repeaters from non-repeaters and a predictive scale for subsequent suicidal behaviour has been constructed and validated (Buglass & Horton, 1974a;Garzotto et al 1976;Si~.ni et al 1979). …”
Section: Introductionmentioning
confidence: 99%